2009
DOI: 10.1348/096317908x314036
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time performance monitoring, goal‐setting, and feedback for forklift drivers in a distribution centre

Abstract: In this study conducted in two auto‐parts after‐market distribution centres, immediate performance goals and feedback were delivered to employees in a warehouse on wireless vehicle‐mounted computers. Engineered labour standards (ELS) calculated work‐unit goal times and presented the driver with immediate performance feedback. Ultimately, the ELS feedback was linked to the company's forklift driver team pallet‐per‐hour quota achievement. Replenishment performance for forklift drivers (N=12) was improved by 2.14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 23 publications
2
16
0
1
Order By: Relevance
“…Furthermore, the visual and audio feedback can increase work quality, as highlighted in the interview and employee satisfaction survey. This agrees with Goomas and Ludwig (2007) and Ludwig and Goomas (2009), which reported work-quality improvement through the reduction of percentage of mispick products.…”
Section: Productivity Work Satisfaction and Quality Improvementssupporting
confidence: 92%
See 3 more Smart Citations
“…Furthermore, the visual and audio feedback can increase work quality, as highlighted in the interview and employee satisfaction survey. This agrees with Goomas and Ludwig (2007) and Ludwig and Goomas (2009), which reported work-quality improvement through the reduction of percentage of mispick products.…”
Section: Productivity Work Satisfaction and Quality Improvementssupporting
confidence: 92%
“…(480 min/442.8 min) × 100% -100% = 8.4%.] This complements the findings of other studies that reported productivity improvements when a visual and audio feedback system was used in an auto parts distribution center Ludwig & Goomas, 2009). However, the prior studies did not address the ergonomics aspects, that is, work satisfaction.…”
Section: Productivity Work Satisfaction and Quality Improvementssupporting
confidence: 86%
See 2 more Smart Citations
“…Conversely, performance monitoring is a useful technique that provides managers a means for obtaining accurate information about employees' performance on a moment by moment basis via direct observation, in comparison to estimating employee performance via self-reporting (Donaldson and Grant-Vallone, 2002;Komaki, 1986). When accurate information is obtained on employee behaviour, managers are able to establish attainable work-and safety-related goals and deliver accurate performance feedback to their employees Ludwig and Goomas, 2009), thus increasing the likelihood that unsafe, inefficient, and ineffective performance is corrected and improved. Even though direct observation of behaviour is an important feature of work sampling, little is known about how direct observation specifically affects subordinates and their behaviour.…”
Section: Introductionmentioning
confidence: 99%